Perception of Cassava Farmers of Climate Change on Cassava Production in Ido Local Government Area of Oyo State, Nigeria - I. O, Oyewo; A.O, Adepoju; E.O, Oyewo; M.O, Adigun (Current Research in Agricultural Sciences, 2017)
The study examined the perception of farmers on the change in climate condition on cassava production in Ido Local Government area of Oyo State. Data were collected through the use of structured questionnaire which were administered to 76 respondents. Descriptive and multiple regression analysis were used to analyse the result of this study. Results showed that 85.8% of the respondents are male and 14.7% were female, 29.2% were between 31-40years, 70.7% of the respondents received information on climate change through neighbours and friends, 100% of the respondents relied on rainfall as a source of water to the farm, 92% made use of manual planting method, while 61.3% of the respondents perceived that climate change does not have absolute effect on cassava production, also majority 50.7% agreed that extension worker do not enhance productivity, major sources of climate change awareness are through radio and television. Regression result showed that labour used was negative and statistically significant at 1%, extension agents visit has a negative coefficient and significant at 5% while source of farm land and farm size has a positive relationship to cassava output in the study. Therefore, extension agent visit or contact should be improved in order to enhance or assist the farmer on how to militate against climatic change and also to help in the adoption of new technology by the farmers in the study area.